Optimization Of Production Combination in Umah Lokal Coffee Roastery - Putu Jenny Natasia; Putu Yudi Setiawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Umah Lokal Coffee Roastery is a business engaged in the production and marketing of coffee beans. This study aims to optimize the production combination to maximize profits using the Linear Programming method. This method enables the company to determine the optimal production quantity for each type of product, namely Telek Beans, Barong Beans, Jauk Beans, Gerbera, and Daisy. The analysis results indicate that the optimal production combination includes producing 128 units of Telek Beans, 155 units of Jauk Beans, 85 units of Gerbera, and 189 units of Daisy, while the production of Barong Beans is discontinued. Implementing this strategy has the potential to increase profits by Rp1,124,417 or 6.4%. This research contributes to the development of more efficient production strategies in dealing with resource constraints.